Influence of CNT, TiO2 and SiC nanostructure additions on microstructural and superconducting properties OF YBa2Cu3O7−δ synthesized using thermal treatment - Barood, Fatma Ali Alfirgan (2023)
Yttrium Barium Copper Oxide YBa2Cu3O7−δ (Y123) has emerged as one of the most promising high-temperature superconductors due to its potential applications in various fields. However, in high magnetic fields, Y123 applications are limited by weak links at grain boundaries, leading to low Jc. In this research, different weight percentages, x = (0.0, 0.2, 0.4, 0.6, 0.8, and 1.0 wt.%) of CNT (2 nm), TiO2 (6 - 15 nm) and SiC (15 nm) nanostructures were added to Y123 bulk prepared using a thermal treatment method. The primary objective is to investigate how the incorporation of these nanostructures influences the structure and superconducting properties of Y123. The samples were characterised using various analytical techniques, including thermogravimetric analysis (TGA), X-ray diffraction (XRD), field emission scanning electron microscopy (FESEM) along with EDX, alternating current susceptibility (ACS), four-point probe technique (4PP) and electron-spin resonance (ESR). The XRD analysis revealed that the samples predominantly consisted of the Y123 phase, which exhibited an orthorhombic crystal structure. Additionally, the Y211 phase was detected in all additional samples as a minor phase. FESEM observations showed that the incorporation of CNT, TiO2 and SiC nanostructures yielded more homogeneous specimens and improved inter-grain connectivity. EDX spectra performed for all Y123 samples showed the presence of Y, Ba, Cu and O elements with a precise match for the standard peak position for these elements. From ACS measurement, the presence of CNT enhanced onset critical temperature (Tc-onset) at x = 0.4 wt.% CNT. Samples with the addition of TiO2 and SiC showed a slight decrease in Tc-onset, while Tcj greatly increased except for the higher contents of SiC. The temperature-dependent resistivity measurements, ρ-T confirmed the occurrence of superconductivity in all samples. However, samples at x = 0.8 and 1.0 wt.% SiC showed semiconducting like behaviour. Tc-onset was observed at 95.6 K for a pure sample, and slightly decreased with the addition of nanostructures due to oxygen modification. The value of Jc as measured by current-voltage measurement was 2.08 A/cm2 for the pure sample and increased to 8.1 A/cm2 for the sample with x = 0.4 wt.% CNT, indicating enhanced grain connectivity. The ESR spectra for all samples displayed a symmetrical signal behaviour. Based on the results obtained, it can be concluded that the incorporation of CNT, TiO2 and SiC nanostructures into Y123 superconductors offers a viable route to enhance the superconducting properties with the best result achieved at x = 0.4 wt.%.CNT.in term of Tc-onset, and Jc.